Biosférické rezervácie ako zdroj pozitívnych externalít - Katarína Vitálišová; Mária Vavrúšová; Katarína Sýkorová (Ekonomika a Spoločnosť)
The advantages of protected areas mainly relate to the evaluation of ecosystem services which provide benefits to people. These affect various areas of life. From the perspective of economic theory, these are externalities. These are perceived as benefits or disadvantages that occur outside the market to another party. Based on the review of literature, this paper highlights the advantages of the biosphere reserves regarding the externalities that arise from their presence as a distinct type of area connecting the principles of environmental protection with suitable socio-economic development. The paper thus contributes to the development of theoretical knowledge, given that this is a poorly researched issue, but at the same time very topical due to climate change and its negative impacts on nature and humans.